Blood and salivary cortisol and testosterone in young cross-country skiers - Kallio, T.; Karvonen, H.; Mäki, M.; Käsmä, J.; Kilpeläinen, P.; Virtanen, V. (3rd International Congress on Science and Nordic Skiing - ICSNS 2015. 5-8 June 2015, Vuokatti, Finland, 2015)
INTRODUCTION: Cortisol is the main glucocorticoid in the body and has a catabolic function inducing the breakdown of muscle proteins and adipose tissue. The cortisol secretion is activated in response to physical and psychological stress. In accordance, also exercise has been shown to increase its secretion (Brownlee et al. 2007). Testosterone is a multifunctional anabolic hormone having an important role in the growth and maintenance of skeletal muscle, bone and red blood cells (Zitzmann & Nieschlag 2001). In athletes, the testosterone/cortisol (T/C) ratio can be used to obtain information on the anabolic-catabolic balance of the body (Adlercreutz et al. 1986) and hence, to evaluate the effect of training load changes on stress and recovery.